THE INFLUENCE OF TPU CIBARUNAI SERVICES ON MANAGEMENT OF BURIAL GROUND BANDUNG CITY - Muhamad Dimas Ferninda; Intan Intan (STIA Bagasasi, 2022)
This study aims to find out how the role of the Bandung City Government regarding services at Cibarunai TPU in Managing Cemetery Land. This study uses a quantitative method through a descriptive approach as part of the response research of an employee at TPU Cibarunai. This study also uses a non-probability sampling technique with a total of 10-15 informants. The results of this study aim to determine the role of the Bandung City government in Cibarunai TPU services in managing Cemetery Land. which is still not optimal in carrying out the division of existing land and officers who are still lacking in socializing directly with the surrounding community so that there are many problems or obstacles that exist. The role of the Regional Government of the City of Bandung as a provider of land is not only as a community service institution but in a democratic society it has a main role, namely providing infrastructure and facilities.